PENGEMBANGAN MODUL KEANEKARAGAMAN HAYATI BERBASIS POTENSI LOKAL PADA TUMBUHAN AREN (ARENGA PINNATA) DALAM PEMBELAJARAN BIOLOGI SMA DI SIPIONGOT - Taufik Al Latifun Srg; Khairuddin Khairuddin; Lailatun Nur Kamalia (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
This study aims to determine the use, validity, and responses of teachers and students from the biodiversity module based on the local potential of sugar palm (Arenga pinnata) plants in high school biology learning in Sipiongot. This study uses Research and Development (R&D) research methods based on the Thiagarajan methodology with four stages, namely define, design, development and disseminate stages. This research was carried out starting from October-January 2022 with a research sample of 15 students of class X SMA N 1 Sipiongot Dolok. The results showed that the sugar palm plant was very beneficial for the village and various fields such as education, health and the community economy. The percentage of the feasibility of the module assessment by material experts is 90%, media experts are 70%, linguists are 79% and the response test of biology teachers (field practitioners) is 78% and student responses are 92%. So it can be concluded that the Biodiversity Module Based on the Local Potential of Sugar Palm Plants (Arenga Pinnata) in high school biology learning in Sipiongot is feasible and practical to use for learning activities.